ANALISIS PENGARUH BUDAYA ORGANISASI, LOCUS OF CONTROL, STRES KERJA TERHADAP KINERJA PEMERINTAH DAERAH DAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING (STUDI EMPIRIS PADA PEMERINTAH KABUPATEN BENGKALIS) - Wahyuni, Endang Sri (Fakultas Ekonomi dan Bisnis, Universitas Riau, 2016)
This study aims to determine the influence of organizational culture, locus ofcontrol, and job stress on local government performance and job satisfaction asan intervening variable in Bengkalis District Government. This research wasconducted in Bengkalis using questioner to 183 respondents, the analysistechnique used is the technique of path analysis.The results showed that: 1) the variable of job satisfaction partially indicates thatorganizational culture, locus of control and job stress has effect on jobsatisfaction. While simultaneously (together) that organizational culture, locus ofcontrol, and the effect of job stress on job satisfaction indicated by the value of Rsquare(R2) 0,556 or 55.6 percent. 2) Furthermore, to the variable of performanceof local governments partially proves that organizational culture, locus of control,job stress and job satisfaction has effect the performance of local governments.While simultaneously (together) shows that organizational culture, locus ofcontrol, job stress and job satisfaction influence on local governmentperformance indicated by the value of R-square (R2) 0.650 or 65 percent.